PENGEMBANGAN MEDIA KARTU UNO PADA PEMBELAJARAN KANJI - Tri Riti Saulia; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out what procedures that carried out in developing UNO card media and it already standardized by experts or validators so it’s suitable for media learning. This study uses a research and development model of R&D using the Sugiyono model. The subjects of this study were 20 students of the Japanese Language Education Study Program level II. The collected data were analyzed using questionnaires. The results of the research are based on five stages: a) Potential Problems b) Data Collecting, c) Product Design, d) Product Validation, e) Product Trial. The eligibility level of UNO card media is based on an assessment by 2 validators which consist material experts and media experts. UNO card media is eligible based on validation result by material experts with an average score of 82,14% in the appropriate category, and then media experts with an average score of 97,91% in the very appropriate category. The product should be revised according to suggestions and input from the experts. UNO card media was tested on students of the Japanese Language Education Study with 81,71% in the very appropriate category for kanji learning.Key Words: Karuta, Kanji, Japanese language education.